Impediments to Nigerian civil service reforms: lessons for ASEAN - Onimisi, Timothy; Ku Samsu, Ku Hasnita; Ismail, Mohd Mahadee; Wan Mohd Nor, Murni (Fakulti Sains Sosial dan Kemanusiaan, Universiti Kebangsaan Malaysia, 2018)
The quest to reform civil service in order to systematically position it for the task of prompt and optimal achievements of the policies of government led to series of reforms across the Association Southeast Asian Nations (ASEAN) and Africa (particularly Nigeria). These civil service reforms began in the colonial era, until the country’s independent and beyond. But unfortunately it has not yet resolved the challenges of inefficiency, low service delivery, salary structure, general welfare issues and political influence inherent in the Nigerian civil service. This paper critically analyzed the major impediments to each and every Nigerian civil service reforms, and the lessons the ASEAN can draw from the Nigeria's experience. The paper relied on secondary sources of data, especially journal articles, reports and text books. The paper found that most of the reforms in the Nigerian civil service are mainly hindered by lack of commitment and political will, which remains the fundamental problem hampering the implementation of various reforms in the service. Hence, political commitment and quality consultant in future civil service reforms would make significantly contribution to the developmental quest of ASEAN through the Nigerian experience.